Evaluation of Toxicological Analysis Results and Treatment Applications in Cases Registered for Drug Addiction at Parole Branch office of Trabzon - Karadeniz, Hülya; Birincioğlu, İsmail; Seçilmişoğlu, Bahattin; Savaş, Hülya; Zazoğlu, Sinan (The Bulletin of Legal Medicine, 2009)
Substance use, increased rapidly all over the world and our country become a very important social problem, to take legal measures were made compulsory parole is the conditional release of a prison inmate after serving part (if not all) of his or her sentence, allowing the inmate to live in the community under supervision of the parole period. Parole and Aid Centers, which were put in effect by Ministry of Justice in the context of membership process of EU, set up as a social service on 20 July 2005 with a law which went into effect after being published in Official Gazette. At this study, 201 (47.2%) cases, which contained drug addiction were examined out of 425 cases in total, which were registered to Branch Directorate of Trabzon Parole between the dates of 21 December 2005 and 30 June 2008. The cases were grouped in terms of age, gender, education level, occupation, drugs used, treatment, and toxicological analysis results. The rates of drug using for men are 98.5% (n = 198), and for women 1.5% (n=3). The ages of cases were ranked between 17 and 64, the average age was found as 32.47 ± 10.55 years. The frequency of drug use is most in the age group of 27-36 (39.8%, n=80). As a result, parole application, which is rather new in Turkey, has puts on the agenda with a chance of being addictive were recovered to the society by being followed and treated. The reluctance of guilty people returning to the prison again, the effect on individual of being considered important by system, and illuminating information which were given by educator, and treatment performance indicate positive effect on the guilty.Key words: Parole, drug, addiction
Keywords: parole; drug; addiction